Category of “Good” in Psychoterapy – an Outline of Issues - Lustig, Rafał (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
Category of “good” in psychotherapy is the main subject of the thesis. Its aim is to problematise the concept of „good” in three perspectives: area, goals and climate of psychoteraphy. It will be done by posing questions about: the human being’ssituation in psychotherapy, the identity of client, the sources of „good” concept’s meaning in psychotherapy, the conflict between various aspects of client's good, the conflict between client's good and the others good, the requirements for the proper psychotherapeutic process and the validation of psychotherapy. The thesis is hermeneutic in its character. It shows the relational nature of “good” with its unavoidable and unsolvable problems.